(6x+1)(4x-6)=45

Simple and best practice solution for (6x+1)(4x-6)=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+1)(4x-6)=45 equation:


Simplifying
(6x + 1)(4x + -6) = 45

Reorder the terms:
(1 + 6x)(4x + -6) = 45

Reorder the terms:
(1 + 6x)(-6 + 4x) = 45

Multiply (1 + 6x) * (-6 + 4x)
(1(-6 + 4x) + 6x * (-6 + 4x)) = 45
((-6 * 1 + 4x * 1) + 6x * (-6 + 4x)) = 45
((-6 + 4x) + 6x * (-6 + 4x)) = 45
(-6 + 4x + (-6 * 6x + 4x * 6x)) = 45
(-6 + 4x + (-36x + 24x2)) = 45

Combine like terms: 4x + -36x = -32x
(-6 + -32x + 24x2) = 45

Solving
-6 + -32x + 24x2 = 45

Solving for variable 'x'.

Reorder the terms:
-6 + -45 + -32x + 24x2 = 45 + -45

Combine like terms: -6 + -45 = -51
-51 + -32x + 24x2 = 45 + -45

Combine like terms: 45 + -45 = 0
-51 + -32x + 24x2 = 0

Begin completing the square.  Divide all terms by
24 the coefficient of the squared term: 

Divide each side by '24'.
-2.125 + -1.333333333x + x2 = 0

Move the constant term to the right:

Add '2.125' to each side of the equation.
-2.125 + -1.333333333x + 2.125 + x2 = 0 + 2.125

Reorder the terms:
-2.125 + 2.125 + -1.333333333x + x2 = 0 + 2.125

Combine like terms: -2.125 + 2.125 = 0.000
0.000 + -1.333333333x + x2 = 0 + 2.125
-1.333333333x + x2 = 0 + 2.125

Combine like terms: 0 + 2.125 = 2.125
-1.333333333x + x2 = 2.125

The x term is -1.333333333x.  Take half its coefficient (-0.6666666665).
Square it (0.4444444442) and add it to both sides.

Add '0.4444444442' to each side of the equation.
-1.333333333x + 0.4444444442 + x2 = 2.125 + 0.4444444442

Reorder the terms:
0.4444444442 + -1.333333333x + x2 = 2.125 + 0.4444444442

Combine like terms: 2.125 + 0.4444444442 = 2.5694444442
0.4444444442 + -1.333333333x + x2 = 2.5694444442

Factor a perfect square on the left side:
(x + -0.6666666665)(x + -0.6666666665) = 2.5694444442

Calculate the square root of the right side: 1.602948672

Break this problem into two subproblems by setting 
(x + -0.6666666665) equal to 1.602948672 and -1.602948672.

Subproblem 1

x + -0.6666666665 = 1.602948672 Simplifying x + -0.6666666665 = 1.602948672 Reorder the terms: -0.6666666665 + x = 1.602948672 Solving -0.6666666665 + x = 1.602948672 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.6666666665' to each side of the equation. -0.6666666665 + 0.6666666665 + x = 1.602948672 + 0.6666666665 Combine like terms: -0.6666666665 + 0.6666666665 = 0.0000000000 0.0000000000 + x = 1.602948672 + 0.6666666665 x = 1.602948672 + 0.6666666665 Combine like terms: 1.602948672 + 0.6666666665 = 2.2696153385 x = 2.2696153385 Simplifying x = 2.2696153385

Subproblem 2

x + -0.6666666665 = -1.602948672 Simplifying x + -0.6666666665 = -1.602948672 Reorder the terms: -0.6666666665 + x = -1.602948672 Solving -0.6666666665 + x = -1.602948672 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.6666666665' to each side of the equation. -0.6666666665 + 0.6666666665 + x = -1.602948672 + 0.6666666665 Combine like terms: -0.6666666665 + 0.6666666665 = 0.0000000000 0.0000000000 + x = -1.602948672 + 0.6666666665 x = -1.602948672 + 0.6666666665 Combine like terms: -1.602948672 + 0.6666666665 = -0.9362820055 x = -0.9362820055 Simplifying x = -0.9362820055

Solution

The solution to the problem is based on the solutions from the subproblems. x = {2.2696153385, -0.9362820055}

See similar equations:

| x^2+2x+4=mx | | 4x+3n=53 | | 3x+2y=66 | | 4x2=2x-1/4 | | 2x-9+3x-1=5 | | 2(x)+7=6 | | 4x2-2x-1/4 | | 18x-2(7x+3)=-38 | | 8+6x=7x+5 | | -17x-3=9x+23 | | 11-(6-4*x)=2/3*x | | 6+1-5=7;2 | | 21/4959=x/21 | | -3x-8+x=-4x+x-10x | | 3x^5-24x^4+12x^3= | | 4.6=3.5w-66 | | 1/2(4x-22)=25 | | 7x-3=5x+8 | | -9(6-u)-2u=-10 | | 5(3)-4=11 | | 6x-7=10x+5 | | 5(-1.4)-4=11 | | (y+9)= | | 5=-x/-2+6 | | 27-6d=7t+4d | | 5=-x/2+6 | | 10-6x=11x-24 | | -28-3x= | | 9y+5(4-9)=39 | | 70-4x= | | 3x+27-8=67 | | 8-8x=68-29x |

Equations solver categories